Tumour necrosis factor haplotypes and asthma. - Moffatt,MF; Cookson,WO (Hum Mol Genet, 1997)
Airway inflammation is a prominent feature of asthma. The pro-inflammatory cytokine Tumour Necrosis Factor shows constitutional variation in its level of secretion, which is linked to polymorphisms within the TNF gene complex and the surrounding MHC. In this study, 413 subjects in 88 nuclear families from a general population sample were examined for association with asthma and TNF polymorphisms. Ninety-two subjects were asthmatic, as defined by questionnaire. Asthma was significantly more common in subjects with allele 1 of the LT alpha NcoI polymorphism (LT alpha NcoI1) (p = 0.005), and allele 2 of the TNF-308 polymorphism (TNF-3082) (p = 0.004). The association was confined to the LT alpha NcoI1/TNF-3082 haplotype, so that it was not possible to differentiate between the effects of LT alpha NcoI and TNF-308 alleles. The HLA-DR locus was excluded as a cause of this association. The results suggest that genetic influences on inflammation may be important in the pathogenesis of asthma.